2007
DOI: 10.1179/174328907x177581
|View full text |Cite
|
Sign up to set email alerts
|

Modification of unsaturated polyesters using polyethylene glycol

Abstract: The fracture toughness and impact resistance of rigid unsaturated polyesters can be modified by various physical and chemical methods. In this study, flexible unsaturated polyesters were prepared by condensation polymerisation of maleic anhydride, phthalic anhydride and propylene glycol in the presence of polyethylene glycol. By this method, copolymers of unsaturated polyesters with polyethylene glycols of different molecular weights were prepared. A two stage process was used for the synthesis, which resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Hence, the exposed degradation for CP-CH has no genuine effect on the macroscopic properties in Figure 5, at least at the selected layer thickness. The chains are still long enough and interacting sufficiently to enable strength and impact [26], the latter specifically at higher temperature.…”
Section: Evaluation Of the Materials Performancementioning
confidence: 99%
“…Hence, the exposed degradation for CP-CH has no genuine effect on the macroscopic properties in Figure 5, at least at the selected layer thickness. The chains are still long enough and interacting sufficiently to enable strength and impact [26], the latter specifically at higher temperature.…”
Section: Evaluation Of the Materials Performancementioning
confidence: 99%
“…Blends of unsaturated polyesters and functional rubbers such as hydroxy terminated polybutadiene, epoxidized natural rubber (ENR), hydroxy terminated natural rubber (NR), and maleated nitrile rubber were studied. It was reported that the elastomers bearing reactive functional groups show better compatibility with the resin and improve the toughness and impact resistance of the cured resin substantially, compared with unmodified elastomers 12, 13…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of the UPRs were evaluated and the results showed that CTBN is the most promising in improving the mechanical properties of the UPRs because the toughness and the impact strength were significantly enhanced, without jeopardizing extensively the remaining properties. Another approach was studied by the same researchers [38], in which poly(ethylene glycol) (PEG) segments were incorporated in the UP structure. The mechanical properties of the ensuing UPRs (35 %wt styrene) were evaluated and the influence of the incorporation of PEG in the UP structure was accessed.…”
Section: Ways To Tailor and Improve The Properties Of The Ups And Uprsmentioning
confidence: 99%